2017
DOI: 10.3389/fmars.2017.00337
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Seasonal Timing of Maine's Lobster Fishery

Abstract: The fishery for American lobster is currently the highest-valued commercial fishery in the United States, worth over US$620 million in dockside value in 2015. During a marine heat wave in 2012, the fishery was disrupted by the early warming of spring ocean temperatures and subsequent influx of lobster landings. This situation resulted in a price collapse, as the supply chain was not prepared for the early and abundant landings of lobsters. Motivated by this series of events, we have developed a forecast of whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…The time series revealed that 2012 season was indeed anomalously early over the study period, but not such an outlier to explain the magnitude of disruption in the lobster industry (Figure ), similar to trends in landings (Mills, Pershing, & Hernandez, ). This reiterates that initial intra‐annual molt timing is only one component of the more complex economic system.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The time series revealed that 2012 season was indeed anomalously early over the study period, but not such an outlier to explain the magnitude of disruption in the lobster industry (Figure ), similar to trends in landings (Mills, Pershing, & Hernandez, ). This reiterates that initial intra‐annual molt timing is only one component of the more complex economic system.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies that concern molt timing have either focused on an area outside the GoM (Northeastern Nova Scotia, Canada; Tremblay & Eagles, ), were conducted in autumn (Thakur et al., ), or they have utilized data that do not directly determine the molt stage of individual lobsters (Mills et al., , ; his study). Therefore, there is no truly descriptive time series for initial intra‐annual molting within the GoM, as previous attempts rely on proxies such as shell condition and color, or landings, with no evaluation available on the relationship between such proxies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several forecasts of phenological events have been developed (Payne et al, ), including one in the GoM of the threshold conditions and timing of when the Maine lobster fishery can be expected to shift into its high landings summer mode (Mills, Pershing, & Hernández, ). This model uses buoy‐based temperature observations and historical fishery data to forecast the timing of the uptick in fishery landings 3–4 months in advance (Mills et al, ). Similar models that rely on temperature observations, biological lags, and historical temperature–biology relationships have been developed in other regions to forecast the timing of salmon runs (e.g., Anderson & Beer, ).…”
Section: Adaptation Strategies Related To Phenologymentioning
confidence: 99%
“…The present study is the third in a series of recently emerging forecasting products applied to the American lobster that range from short‐term, seasonal‐scale (Mills et al. ) to long‐term, decadal‐scale forecasts (Le Bris et al. ).…”
Section: Introductionmentioning
confidence: 99%